Re-Invented Tradition: Exploring the Contribution of Quranic Competition on Arabic Language Use and Learning in Northern Nigeria - Yahaya, Nasir; Samaila, Ali; Abdulganiyu, Mubarak Lawal; Adam, Faiz Shuaibu (IJELR: International Journal of Education, Language, and Religion, 2024)
The trend of Qur’anic recitation competitions, popularly known as Musabaqah, has grown rapidly across the Muslim globe since its inception at the international level in Malaysia in 1961 as a way to display the importance and value of Quranic recitation and memorization and inspire Muslims to do their best to understand and cherish the divine message of the Quran. This study examines Musabaqah's contribution to promoting Arabic in northern Nigeria, with a focus on Kaduna State. The research uses a qualitative method to collect data through observation and interviews with selected individuals within the state. The findings indicate that Musabaqah has a positive impact on Arabic language learning and use in the state, as it creates a competitive spirit among Muslims to learn more about the Arabic language in order to have a better understanding of the Quran and its sciences and increases community interest in learning Arabic. Therefore, the study recommends that the Nigerian Ministry of Education, in collaboration with the bodies regulating Musabaqah and teaching Arabic and Islamic studies, organize seminars and workshops that promote Arabic and preserve its cultural heritage. Finally, offering incentives, awards, and scholarships will motivate the competitors and enhance their capacity to participate favourably with any of their counterparts globally.